2020
DOI: 10.3390/children7080095
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Promotion among Adolescents: Effects of a Jump Rope-Based Physical Activity Afterschool Program

Abstract: The major purpose of this study was to examine the effects of a jump rope-based physical activity afterschool program on middle school students’ physical fitness. Sixty students (Mage = 13.37, SD = 0.58; 53.3% female) participated in a 12-week jump rope-based afterschool program (45 min/time, three times/week). Participants were randomly assigned to three groups: (a) freestyle rope skipping (N = 20), traditional jump rope (N = 20), and a control group (N = 20). Physical fitness tests, including muscular streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
(51 reference statements)
3
19
0
Order By: Relevance
“…This finding is consistent with the ORANGE project by Kumaravel V et al, 2014 at Chennai, which concluded that the prevalence of overweight/obesity was 26.4% among children aged 6-11 years [21]. Regarding the prevalence of hypertension, many studies conducted by various researchers [17][18][19][20]22], including the present study, found that hypertension was significantly high among overweight and obese adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with the ORANGE project by Kumaravel V et al, 2014 at Chennai, which concluded that the prevalence of overweight/obesity was 26.4% among children aged 6-11 years [21]. Regarding the prevalence of hypertension, many studies conducted by various researchers [17][18][19][20]22], including the present study, found that hypertension was significantly high among overweight and obese adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with the ORANGE project by Kumaravel V et al, 2014 at Chennai, which concluded that the prevalence of overweight/obesity was 26.4% among children aged 6-11 years at Chennai (21). Regarding the prevalence of hypertension, many studies conducted by various researchers (17)(18)(19)(20)22) including the present study found that the prevalence of hypertension was significantly high among overweight and obese adolescents.…”
Section: Table 5: Regression Model Describing the Effect Of Bmi On Demographic Variables Of Study Group Pretest Post Test-1 Post Test -2supporting
confidence: 53%
“…To prevent a decrease in PA, various interventional programs have been constructed to encourage children and adolescents to be more physically active [ 10 , 11 ]. Since such programs should be motivational and attractive, dance is a perfect tool, as it fulfils not only PA requirements but also enables the development of social skills and expressiveness in youth [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%